2022
DOI: 10.1088/1741-4326/ac9916
|View full text |Cite
|
Sign up to set email alerts
|

A reduced model for the ITER divertor based on SOLPS solutions for ITER Q = 10 baseline conditions: A. identifying options for the control parameters*

Abstract: Edge codes such as SOLPS coupled to neutral codes such as EIRENE have become so comprehensive and sophisticated that they now constitute, in effect, ‘code-experiments’ that, as for actual experiments, can benefit from interpretation using simple models and conceptual frameworks, i.e. reduced models. The first task is the identification of options for the reduced model control parameters that are best suited for control of the action of the divertor, i.e. for control of target power loading and sputter-erosion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…However, it has recently been found that in almost all cases (both experimental and computational), these can be represented by functions that depend primarily on the target electron temperature, T e,t [6,14,15]. In this work, we make use of volumetric loss terms that are fit to the aforementioned large database of SOLPS-ITER simulations of the ITER divertor [12], fitting to the electron temperature in the last cell in front of the target on the computational grid used in the modeling. These fits take the form of a 4th-order log-log polynomial:…”
Section: The Reverse 2-point Model (Rev2pm)mentioning
confidence: 99%
See 4 more Smart Citations
“…However, it has recently been found that in almost all cases (both experimental and computational), these can be represented by functions that depend primarily on the target electron temperature, T e,t [6,14,15]. In this work, we make use of volumetric loss terms that are fit to the aforementioned large database of SOLPS-ITER simulations of the ITER divertor [12], fitting to the electron temperature in the last cell in front of the target on the computational grid used in the modeling. These fits take the form of a 4th-order log-log polynomial:…”
Section: The Reverse 2-point Model (Rev2pm)mentioning
confidence: 99%
“…These fit functions are plotted versus T e,t in figure 1. The fit functions are clamped to their maximum for T e,t values above the range used to define these fits in [12] (about 13 eV), though this assumption has negligible effect on any of the results presented in this paper.…”
Section: The Reverse 2-point Model (Rev2pm)mentioning
confidence: 99%
See 3 more Smart Citations